Challenges and uncertainties of ex ante techno-economic analysis of low TRL CO2 capture technology: Lessons from a case study of an NGCC with exhaust gas recycle and electric swing adsorption. (15th December 2017) - van der Spek, Mijndert; Ramirez, Andrea; Faaij, André
Highlights: The challenges of techno-economic analysis of very low TRL technologies are explored. Hybrid approaches to project future performance of low TRL technologies are proposed. Electric swing adsorption is infeasible to economically capture CO2 from an NGCC. Abstract: this work addresses the methodological challenges of undertaking techno-economic assessments of very early stage (technology readiness level 3–4) CO2 capture technologies. It draws lessons from a case study on CO2 capture from a natural gas combined cycle with exhaust gas recycle and electric swing adsorption technology. The paper shows that also for very early stage technologies it is possible to conduct techno-economic studies that give a sound first indication of feasibility, providing certain conditions are met. These conditions include the availability of initial estimates for the energy use of the capture technology, either from bench scale measurements, or from rigorous process models, and the possibility to draw up a generic (high level) equipment list. The paper shows that for meaningful comparison with incumbent technologies, the performance of very early stage technologies needs to be projected to a future, commercial state. To this end, the state of the art methods have to be adapted to control for the development and improvements that these technologies will undergo during the R&D cycle. We call this a hybrid approach. The paper also shows that CO2 capture technologies always need to be assessed in sympathy with the CO2 source (e.g. power plant) and compression plant, because otherwise unreliable conclusions could be drawn on their feasibility. For the case study, it is concluded that electric swing adsorption is unlikely to become economically competitive with current technologies, even in a highly optimised future state, where 50% of the regeneration duty is provided by LP steam and 50% by electricity: the net efficiency of an NGCC with EGR and optimised ESA (49.3%LHV ; min–max 45.8–50.4%LHV ) is lower than that of an NGCC with EGR and standard MEA (50.4%LHV ). Also, investment and operational costs are higher than MEA, which together with ESA's lower efficiency leads to an unfavourable levelised cost of electricity: 103 €/MWh (min–max 93.89–117.31 €/MWh) for NGCC with ESA, versus 91 €/MWh for NGCC with MEA.